"Infectious Supercarelessness" in Discussing Antibiotic-Resistant Bacteria - Neil S. Greenspan (Case Western Reserve University, 2016)
Many bacterial pathogens are exhibiting resistance to increasing numbers of antibiotics making it much more challenging to treat the infections caused by these microbes. In many reports in the media and perhaps even in discussions among physicians and biomedical scientists, these bacteria are frequently referred to as "bugs" with the prefix "super" appended. This terminology has a high potential to elicit unjustified inferences and fails to highlight the broader evolutionary context. Understanding the full range of biological and evolutionary factors that influence the spread and outcomes of infections is critical to formulating effective individual therapies and public health interventions. Therefore, more accurate terminology should be used to refer these multidrug-resistant bacteria.